Validity of arthroscopic measurement of glenoid bone loss using the bare spot - Miyatake K; Takeda Y; Fujii K; Takasago T; Iwame T (Dove Medical Press, 2014)
Katsutoshi Miyatake, Yoshitsugu Takeda, Koji Fujii, Tomoya Takasago, Toshiyuki Iwame Department of Orthopaedic Surgery, Tokushima Red Cross Hospital, Komatsushima, Tokushima, Japan Purpose: Our aim was to test the validity of using the bare spot method to quantify glenoid bone loss arthroscopically in patients with shoulder instability. Methods: Twenty-seven patients with no evidence of instability (18 males, nine females; mean age 59.1 years) were evaluated arthroscopically to assess whether the bare spot is consistently located at the center of the inferior glenoid. Another 40 patients with glenohumeral anterior instability who underwent shoulder arthroscopy (30 males, ten females; mean age 25.9 years) were evaluated for glenoid bone loss with preoperative three-dimensional computed tomography (3D-CT) and arthroscopic examination. In patients without instability, the distances from the bare spot of the inferior glenoid to the anterior (Da) and posterior (Dp) glenoid rim were measured arthroscopically. In patients with instability, we compared the percentage glenoid bone loss calculated using CT versus arthroscopic measurements. Results: Among patients without instability, the bare spot could not be identified in three of 27 patients. Da (9.5±1.2 mm) was smaller than Dp (10.1±1.5 mm), but it was not significantly different. However, only 55% of glenoids showed less than 1 mm of difference between Da and Dp, and 18% showed more than 2 mm difference in length. The bare spot could not be identified in five of 40 patients with instability. Pearson's correlation coefficient showed significant (P<0.001) and strong (R2=0.63) correlation in percentage glenoid bone loss between the 3D-CT and arthroscopy method measurements. However, in ten shoulders (29%), the difference in percentage glenoid bone loss between 3D-CT and arthroscopic measurements was greater than 5%. Conclusion: The bare spot was not consistently located at the center of the inferior glenoid, and the arthroscopic measurement of glenoid bone loss using the bare spot as a landmark was inaccurate in some patients with anterior glenohumeral instability. Level of evidence: Level II, prospective comparative study. Keywords: shoulder instability, glenoid defect, arthroscopy, Bankart repair, 3D-CT, bone graft, shoulder dislocation